Diabetes Mellitus Predicts Weight Gain After Surgery in Patients With Acromegaly - Jang, Han Na; Kim, Yong Hwy; Kim, Jung Hee (Frontiers in Endocrinology, 2022)
Objective Metabolic complications are common in patients with acromegaly. However, this occasionally does not improve post-surgery and may be related to postoperative weight gain. We aimed to investigate the postoperative weight change and factors associated with postoperative weight gain in patients with acromegaly. Design and Methods Overall, 113 consecutive patients with body weight records pre- and 3–6 months post-surgery between October 2009 and March 2021 were enrolled. Patients were divided into three groups: weight loss (weight decrease ≥3%), stable, and weight gain (weight increase ≥3%). Hormone status, metabolic comorbidities, and anthropometric parameters were compared between the groups. Results Among 113 patients, 29 (25.7%) and 26 (23.0%) patients lost and gained weight, respectively, post-surgery. There were no significant differences in baseline characteristics, including age at diagnosis, sex, body mass index, and growth hormone levels among the three groups. The prevalence of diabetes mellitus at diagnosis was significantly higher in the weight gain group than in the other groups. Patients with diabetes (n=22) had a 5.2-fold higher risk of postoperative weight gain than those with normal glucose tolerance (n=37) (P=0.006). In the diabetes mellitus group, the percentage lean mass decreased (-4.5 [-6.6–2.0]%, P=0.002), and the percentage fat mass significantly increased post-surgery (18.0 [4.6–36.6]%, P=0.003), whereas the normal glucose tolerance group did not show body composition changes post-surgery. Conclusion In patients with acromegaly, 23% experienced ≥3% weight gain post-surgery. Diabetes mellitus at diagnosis is a significant predictor of weight and fat gain post-surgery.